The tourism and economic importance of the tourism components in the dreikish erea in Tartous covernorate using geographic information systems(Gis) - ناصر, لميس (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Dreikish region has tourist impotance as it contains agroup of natural tourist attractions that attract tourists who love nature and the green environment ,spread throughout the terrain of the region aroundit , it contains many human tourist attraction remaining to date , which reflect the historical record of the region over time , and are attaractive to tourists who love historical monuments. From various parts on of the governorate ,its economic importance is crystallized by iIts important geographical loction, as it represents the central region of tartous covernorate , and is considered a main geteway to Hama covernorate (masyaf) via the Dreikish - Masyaf road ,and the Tartous - Dreikish hign way ,in addition to its richness in springs and caves that attract investments from the public and private sectors , this will have apositive impact on improving the populations standard of living, providing jod opportunities for young people ,supporting the national economy , and achieving comprehensive development in the region. Through this study, the tourism and economic importance of the natural and human tourism components that the Dreikish region embraces , and their geeogrphical distribution in the Dreikish region were determined using geeographical information systems, the prospects for its development were also studied in a way that maintains its sustainability , and the researcher concluded that there are many natural and human sites of tourist importance, and economic development in the region , which contributes to increasing tourism revenues , but it lacks tourism services and the direction of the distribution of landmark ,and tourist sites is spread longitudinally , stanting towards the northeast throughout the region.